CLINICAL AND IMMUNOLOGICAL SUBSTANTIATION OF β-CAROTENE USE IN PRE-SCHOOL CHILDREN - S.O. Klyuchnikov; A.P. Prodeus; I.A. Snimshchikova ("Paediatrician" Publishers LLC, 2010)
The article presents the results of an observation of pre-school children, treated with -carotene (Vetoron) in complex of sanitary measures. Special immunological examination showed that the medication has not specific stimulating influence on immune system in children 3-6 years old. The advisability of its administration as a non-specific medication for the prophylaxis of respiratory diseases is confirmed by the increase of ?-interferon production, probably due to non-specific activation or modulation of NK-cells. Key words: children, β-carotene, interferon. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):32-36)